SURVEI MOTIVASI BELAJAR SISWA MATA PELAJARAN PENDIDIKAN JASMANI OLAHRAGA DAN KESEHATAN MELALUI PERMAINAN TRADISIONAL - Endrawan, I Bagus; Gunawan, Feri Aji (Jurnal Ilmiah Bina Edukasi, 2017)
The method in this study is a survey method. The results showed that the average intrinsic factor in participating in physical education through traditional game activities in SMPN 2 Mesuji 2016 is able to influence the motivation in participating in physical education in the low category of 37.5, while the average extrinsic factors also can influence the motivation to participate in education body in the low category of 14.9. So on average lower intrinsic factor influence on the students motivation is low due to the spirit of siswa 37.5, 17.3 low self-actualization, low physical condition 9.4, laziness is a low 4.3, pleasure Low 24 3, and honest attitude a low 8.4. While the average extrinsic factors considered low due to the efforts of the teacher's low of 14.9, giving praise and reward low of 13.9, lower infrastructure 5.3, and cooperation between friends who low of 13.7.